Mechanism of Solvation in Solvent Alcohols - Jessy, J.M. (Asian Journal of Chemistry, 2010)
Differential solvation of the different species in reactions are treated in two parts: primary differential solvation involving the functional group of the solvent and secondary differential solvation representing substituent effect on the solvation bond. Aliphatic alcohols of α-series (with changing methyl substitution at α-position), as solvents for a number of solvation-based reactions, are studied. Quantitative correlation, between reactivity parameters in the solvents and the polar and ponderal substituent parameters of the alkyl substituents in the solvents, has been shown to be leading to the identification of solvation bonds of two modes—one of electrostatic, and the other of orbital, interactions between the solute and the solvent. Such detailed study of the "mechanism of solvation" is shown to lead to a few interesting mechanistic inferences.